Pemberdayaan Petani Menuju Pertanian Berkelanjutan - Hermawan, Irfan Dwi; Candra, Sahid Mardhika; Azmi, Azzam Muhamad Ulul; Muliawati, Nesha Adinda; Putri, Sabrina Adila; Maharani, Nabilah; Dewi H, Salsabila Puspa; Hartomo, Lalita Chairunnisa; Faraby, Hafiz Ahmad; Rabbani, Azizan Zaki; Muzamil, Sanupal (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
The community service carried out in Dusun Karangasem, Desa Kopen, Kecamatan Teras, Kabupaten Boyolali, Central Java, aimed to empower local farmers and producers of rambak crackers by transforming the waste from garlic peel, which is produced during the rambak cracker production, into an environmentally friendly natural pesticide. This activity was carried out through a series of events, starting with socialization on the importance of using natural materials in pest control, followed by a demonstration of how to make botanical pesticides, and practical training on applying the pesticide to local agricultural land. Through this activity, 85% of the participants were able to independently produce the pesticide using locally available materials. In addition, 75% of the participants reported a significant decrease in pest attacks on their plants after using the natural pesticide. This program not only successfully addressed pest problems but also raise community awareness about the importance of waste management and the application of sustainable, environmentally friendly farming practices. The success of this program also had a positive impact in terms of improving participants' skills and knowledge regarding more efficient and environmentally friendly agricultural management. Additionally, the active involvement of the community in the process of making and applying the natural pesticide demonstrated that this activity could inspire them to be more independent in addressing the challenges they face, especially in pest control without relying on chemical substances. This program is expected to serve as a model that can be applied in other areas to improve farmers' welfare, reduce dependence on chemical pesticides, and promote the concept of sustainable agriculture. Furthermore, the success of using a natural pesticide made from garlic peel waste opens up opportunities for further research to explore the potential of other natural materials in addressing various agricultural challenges in the future